Digital Enlightenment Yearbook 2012 - Bus, Jacques (IOS Press, 2014)
By the end of the 17th century, members of an emerging “European international republic of letters” were becoming increasingly aware that, collectively, they were a force in the world. Birmingham’s Lunar Society brought together merchants and intellectuals discussing openly in coffee houses in much the same way as the barbershop loiterers did during the golden age of Greece.